Academic libraries in COVID-19: a renewed mission for digital literacy. Issue 4 (23rd December 2020) - Martzoukou, Konstantina
Abstract : Purpose: The COVID-19 pandemic has placed online learning, blended or hybrid provision as the "new normal" in Higher Education. For most universities and their academic libraries, especially those with a less strong online presence, the pandemic has caused numerous challenges. However, it has also been a catalyst for change and resifting of priorities. For academic librarians involved in the delivery of information skills/literacy training, a renewed mission is emerging, addressing access and connectivity to resources, designing for online education and fostering the development of digital literacy of students. Design/methodology/approach: This is a conceptual paper based on the author's personal experiences and subjective opinion as a Library and Information Science educator with considerable expertise in online distance learning in the UK. Reflecting critically on the impact of the pandemic from an educational point of view and on key changes experienced, the paper centres on the argument that academic librarians could emerge as strategic partners in Higher Education, towards the direction of enhancing students' digital competences development. Findings: The complete and involuntary shift to online learning due to COVID-19 restrictions has opened the door to multiple challenges in Higher Education, which are complex and ongoing: the implementation of remote tools and practices en masse in online teaching and learning in a way that ensures accessibility and equity for all, issues connecting to online pedagogy and how to prepare students with the information and digital literacy competences required for the new online learning "normal". As academic libraries move forward, they have a renewed mission to help learners in the online space to become both information rich and digitally competent. There is an opportunity to act as the connecting link that will help to move a step forward a strategic vision that places design for equity at the centre of education. Originality/value: The impact of COVID-19 within Higher Education and academic libraries more specifically, is a theme that has not been yet sufficiently discussed, researched or critically debated as the world is still currently going through the pandemic crisis. This paper aims to initiate some early thoughts and conversation, as well as put forward the author's personal critical positioning on the issues, challenges and potential opportunities, emerging in the current educational climate for academic librarians, and to highlight areas of importance for the design and direction of information and library science curricula.